Precision spraying technologies for orchard crops - Thorat, Deepak Sabaji; Jyoti, Bikram; Khadatkar, Abhijeet (Indian Horticulture, 2022)
Crop protection using pesticide application equipment in orchards is a challenging task. Pesticides have become critical input for crop production, therefore efficient pesticide application is important. It is difficult to completely imagine the levels and security of today's crop yields without the use of pesticides. More precise spraying technologies such as Electrostatic spraying system (ESS) and Variable rate spraying has crucial role to play in future agriculture, considering reduction of input cost, environmental concern and safety of human health.